Pengaruh Campuran Bahan Bakar Oli Bekas dan Biosolar Terhadap Emisi Gas Buang pada Mesin Diesel Modifikasi: Analysis of The Effect of Modified Diesel Engine Power With Mix of Used Lubricants and Biosolar On Exhaust Emissions - Sasmita, Aryo (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
The Production Laboratory of the Department of Mechanical Engineering, University of Riau has modified the diesel engine used as a used oil-fueled generator, the problem is the exhaust gas emissions produced, namely the opacity exceeds the quality standard that has been set. The purpose of this study was to determine the calorific value of a mixture of used fuel oil and biodiesel, to determine the relationship between the power generated from the diesel engine as a generator and the emissions produced. This research was conducted by direct measurement of the emissions produced by the diesel engine using a gas analyzer, by operating the diesel engine for 30 minutes and measuring emissions every 5 minutes. This study also varied the power load, namely at idle conditions of 0 W, 1000 W, and a maximum power of 2000 W. The calorific value was tested using a bomb calorimeter. The emission test results from the Dongfeng Model R175 diesel engine which uses a mixture of used fuel oil and biodiesel as fuel show that the CO, CO2, HC and Opacity emissions released on average increase with the length of operating time of the diesel engine and the highest emissions occur when power of 2000 W. The highest level for CO emissions is 0.0161%, for CO2 emissions is 3.53%, for HC emissions is 28.61 ppm, and for opacity is 44.85 % for B30 fuel when the engine is running. operates with a power load of 2000W. The Opacity value of this variation of fuel has exceeded the quality standard that has been set in accordance with Attachment 1 of PERMEN LH No. 5 of 2005 by 40%, but emissions from other variations are still below the quality standard.